The French Cultural Tourism: Exploring the Harmonious Coexistence of Tradition and Modernization - I Wayan Sukma Winarya Prabawa; Putu Ratih Pertiwi; Putu Sucita Yanthy (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2023)
Cultural tourism has become the doctrine of tourism development in many countries. Various local commodities have been transformed into tourist attractions to satisfy the curiosity of tourists. Unfortunately, cultural tourism in many destinations tends to be exclusive, where its activities focus on presenting artificial cultural attractions that are packaged for tourists. This article describes the best practice of how France has succeeded in developing a culture-based tourism sector amidst the demands of modernization and industrialization. Through a qualitative descriptive approach, data and information were collected from observation, literacy studies, and interviews. The authors conducted a thematic analysis to portray a culture-based French tourism model. The analysis results conclude that French tourism is firmly supported by a wealth of culture and traditions that have long been rooted in people's lives.